Self-cleaning compact heat exchangers: The role of two-phase flow patterns in design and optimization. (March 2019) - Maggiolo, Dario; Sasic, Srdjan; Ström, Henrik
Highlights: A novel design of self-cleaning heat exchangers based on two-phase flow optimization. Uniform dropwise condensation facilitates self-cleaning mechanisms of the surfaces. Moderate Jakob and capillary numbers as optimal flow conditions for self-cleaning. Abstract: Fouling on heat exchanger surfaces significantly impedes heat recovery from exhaust gases in many industrial applications. An introduction of the process of self-cleaning possibly represents an efficient solution to this well-known problem. Even if special treatments of the surfaces can help to protect them from fouling, it is still not well understood how to properly design heat exchangers in order to promote the self-cleaning process. In the present study, we investigate by means of Lattice-Boltzmann-based simulations the pivotal role of two-phase flow patterns and condensation-related phenomena in understanding the mechanisms that promote the self-cleaning, and, consequently, a stable heat recovery. In particular, we identify optimal flow conditions and two-phase flow characteristics that allow a clean and efficient operation of compact heat exchangers. Our results indicate that low heat duties and flow rates, which induce the condensation of small and motile droplets able to collect gas impurities, are beneficial for provoking and sustaining self-cleaning mechanisms. We therefore suggest that an effective design of self-cleaning heat exchangers should primarily be governed by principles of two-phase flow, rather than by the heat transfer duty. This work thus represents a step forward in identifying and proposing a procedure for an optimal design of heat exchangers to facilitate an effective heat recovery process from a wider range of exhaust gas mixtures.